Finding a New Home for Islet Cell Transplants. Issue 7 (July 2016) - Coates, P. Toby; Grey, Shane T.
Abstract : Coates and Grey comment of the experimental findings by Pepper et al and discuss the potential utility of a vascularized subcutaneous space for islet transplantation.